Strategi Pembudayaan Entrepreneurship Dalam Membangun Usaha Bisnis Pesantren Berbasis Alumni Network Forum - Miftahkul Jannah; Nur Kholifah; Ach Faqih Supandi (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
Pesantren as a sub-culture of the archipelago that has a great tradition is expected to play a role in this era of globalization. Globalization that adheres to the notion of liberalism encourages people to become entrepreneurs independently. In this condition, several subcultures must move to create a community entrepreneur culture. One of them is the Darul Ulum Islamic Boarding School, Banyuanyar Pemekasan, Madura. This Islamic boarding school, which has thousands of alumni, has succeeded in formulating a business unit development strategy. Everything is done by relying on the alumni forum network.